Development of Salt Hydrolysis Module Based on Problem Based Learning Integrated with TPACK to Improve Numeracy Literacy Skills of Phase F SMA Students - Putty Zinda Febrila; Yerimadesi; Andromeda; Alizar (Postgraduate, University of Mataram, 2024)
This research aims to analyze the validity, practicality and effectiveness of the salt hydrolysis module based on problem based learning integrated with TPACK on students numeracy literacy skills. The development model used is the 4-D model. The module developed was validated by two lecturers and three chemistry teachers. The practicality testing of the module was carried out by three chemistry teachers and 32 SMA students. Testing the effectiveness of the module was carried out using a pre-experimental method with a non-equivalent control group design. The validity test was analyzed using the Aiken's V formula where content and construct validity were obtained respectively 0.91 and 0.92 with the valid category. The practicality test was analyzed using the Aiken's V formula where the practicality scores for teachers and students were obtained respectively 0.94 and 0.86 in the practical category. The module effectiveness test was analyzed using N-Gain where an N-Gain value of 0.76 was obtained in the high category. Based on the results of data analysis, it can be concluded that the salt hydrolysis module based on problem based learning integrated with TPACK developed is valid, practical and effective to improve the numeracy literacy skills of Phase F SMA students.